2021
DOI: 10.1002/ijc.33873
|View full text |Cite
|
Sign up to set email alerts
|

The effects of TNF‐α/TNFR2 in regulatory T cells on the microenvironment and progression of gastric cancer

Abstract: TNFR2 + regulatory T cells preferentially accumulate in the tumor microenvironment, express high levels of immunosuppressive molecules and possess strong suppressive activity. Our study aimed to explore the characteristics and role of TNFR2 + Tregs in the microenvironment and progression of gastric cancer via polychromatic immunofluorescence, single-cell RNA sequencing and flow cytometry assays. The TNFR2 + Treg infiltration level in the tumor microenvironment increased significantly as gastric cancer progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 46 publications
0
27
0
2
Order By: Relevance
“…have also confirmed that TNFR2 + Tregs (Figure 1 ) preferentially accumulate in TME of GC, which express high levels of CTLA‐4 and CCR6 and possess strong suppressive activity by activating the TNF‐α/TNFR2 signaling pathway. 199 In addition, the higher level of TNFR2 + Treg infiltration was correlated to a poorer prognosis in GC patients. Based on the results, targeting TNFR2 + Tregs may be an immunotherapeutic strategy for GC.…”
Section: Treg Subsets In Tumor Immunitymentioning
confidence: 98%
“…have also confirmed that TNFR2 + Tregs (Figure 1 ) preferentially accumulate in TME of GC, which express high levels of CTLA‐4 and CCR6 and possess strong suppressive activity by activating the TNF‐α/TNFR2 signaling pathway. 199 In addition, the higher level of TNFR2 + Treg infiltration was correlated to a poorer prognosis in GC patients. Based on the results, targeting TNFR2 + Tregs may be an immunotherapeutic strategy for GC.…”
Section: Treg Subsets In Tumor Immunitymentioning
confidence: 98%
“…For instance, activation of TNFR1 by TNFα can lead to tumor cell death but under a different set of conditions it can contribute to cancer inflammation and enhance tumor progression. A similar enigma was observed for TNFR2+ tumor-infiltrating lymphocytes (TILs): TNFR2-mediated signals support the survival/activation of CD4+ T regulatory cells (Tregs) and aggravate disease course ( 46 , 60 67 ); however, in triple-negative breast cancer (TNBC) patients, TNFR2+ TILs were associated with improved patient survival. In parallel, mouse studies have connected reduced TNBC growth after chemotherapy with elevated presence of CD8+ TNFR2+ TILs, presumably cytotoxic T cells (CTLs) ( 68 , 69 ), agreeing with TNFR2 being required for cytotoxic activities of CD8+ T cells ( 66 ).…”
Section: The Complexity Of the Tnfα-tnfr Network – What Is The Road M...mentioning
confidence: 83%
“…Then, the roles of each family member should be precisely identified in each cancer type/subtype, prior to treating patients with modulators of the pathway. This can be well-exemplified by taking the TNFR2+ TIL population as a test case: the fact that unlike published reports on the Treg identify of CD4+ TNFR2+ lymphocytes ( 46 , 60 67 ), TNFR2+ TILs were connected to improved survival in TNBC patients and with potential cytotoxic activities of CD8+ TNFR2+ TILs in mouse TNBC tumors ( 68 , 69 ), suggests that targeting TNFR2 in chemotherapy-treated TNBC patients may be harmful; administration of TNFα inhibitors may reduce the proliferation of CD8+ TNFR2+ CTLs and limit the potential of raising potent immune activities against the cancer cells. The detrimental consequence that may be driven by such treatments may explain the findings obtained in TNFα-/- mice that could not mount T cell-mediated anti-tumor effects ( 87 ).…”
Section: Discussion – the (Personalized) Road Aheadmentioning
confidence: 99%
“…Along with all these findings, Jiang et al (2022) and Kumar et al (2022) confirmed that with tumor progression the tissue microenvironment changes from predominance of proinflammatory effectors to predominance of immunosuppressive Tregs (34,35). Qu et al (2022) identified a distinct Treg phenotype that is increased in tumor tissue compared to patientmatched blood and defined by enriched expression of the TNF receptor superfamily member 1B (TNFR2) (30). TNFR2 + Tregs were found to be functionally immunosuppressive and an increased infiltration into tumor tissue correlated with poor prognosis.…”
Section: T Cellsmentioning
confidence: 87%
“…Among the published scRNAseq gastric cancer works, it is apparent that they have undertaken various approaches to their studies. Most groups obtained primary gastric cancer tissues from patients to generate scRNAseq data (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Some utilized previously published primary tumor datasets for further analysis (36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%